Vibration characteristics analysis of fluid-conveying pipes concurrently subjected to base excitation and pulsation excitation. (15th April 2023) - Guo, Xumin; Gao, Peixin; Ma, Hui; Li, Hui; Wang, Bo; Han, Qingkai; Wen, Bangchun
Highlights: A modified transfer matrix model is proposed to solve the vibration response of FCPs under base and pulsation excitations. The proposed model is verified by the shaking table experiments of two FCPs. The effects of some parameters on PFCPs under base and pulsation excitations are explored. The effect of coupling stiffness on vibration transmission of PFCPs is analyzed. Abstract: Previous studies mostly concentrated on the vibration characteristics of the fluid-conveying pipe (FCP) under a single excitation, which is insufficient to address the requirements of FCP vibration analysis under a complex load environment. Meanwhile, the aero-engine pipes may be affected by both base and pulsation excitations during operation, which could result in more complicated vibration behaviors. To solve the vibration response of FCPs concurrently subjected to base excitation and pulsation excitation, a modified transfer matrix model is proposed in this study. The proposed model overcomes the shortcoming that the traditional transfer matrix model (TMM) can only be utilized to analyze the frequency response of FCP under point excitation or pulsation excitation. By modifying the pipe's governing equation, the base excitation is introduced into the whole pipe segment in the form of the external excitation vector. The proposed model is validated by comparing the collected vibration signals and simulation results of a straight FCP and L-shaped FCP under base excitation and pulsation excitation. Then, the study is further extended to the parallel fluid-conveying pipes (PFCPs), and the influences of base excitation amplitude, flow velocity, pressure, coupling stiffness, and dual clamp damping on the vibration characteristics of PFCPs are analyzed. This work can provide an efficient and general solution for vibration prediction of complex fluid-conveying pipes subjected to base and pulsation excitations in engineering.